PENDAMPINGAN PEMBUATAN DAN PENGELOLAAN LEARNING MANAGEMENT SYSTEM DI SMA NEGERI 4 KOTA LANGSA - Akram, Rizalul; Munawir; Novianda; Cut, Banta (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2023)
Learning Management System (LMS) is an important supporter of the continuity of the online teaching and learning process and also makes it easier for students to access learning content from anywhere and at any time. Apart from making it easier for students to access learning materials, this LMS also makes it easier for students to access assignments. given by the teacher. Based on an analysis of the situation of several schools in Langsa City, SMA Negeri 4 Langsa City was chosen because it did not have an LMS, therefore the PKM team chose SMA Negeri 4 as the PKM partner for this matter. This activity is carried out by providing training and assistance to operators and school teachers. It is hoped that in the future this LMS can be used by SMA Negeri 4 for the blended learning learning process and become an example of application for other schools in the future.